2022
DOI: 10.1002/essoar.10509434.2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Importance of Lake Emergent Aquatic Vegetation for Estimating Arctic-Boreal Methane Emissions

Abstract: Areas of lakes that support emergent aquatic vegetation emit disproportionately more methane than open water but are under-represented in upscaled estimates of lake greenhouse gas emissions. These shallow areas are typically less than ∼1.5 m deep and can be detected with synthetic aperture radar (SAR). To assess the importance of lake emergent vegetation (LEV) zones to landscape-scale methane emissions, we combine airborne SAR mapping with field measurements of vegetated and open-water methane flux. First, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…Jeffrey et al (2019 a ) found that emissions from the emergent vegetated habitat accounted for 59% of the annual CH 4 emissions in an Australian subtropical wetland, followed by diffusion (21%) and ebullition (20%). Kyzivat et al (2022) also demonstrated the importance of including emergent macrophyte emissions, since accounting for their coverage increased lake CH 4 emission estimates by more than 21% in a subarctic‐boreal region. In our study, CH 4 emission from the vegetated habitat was also a very important pathway in clear lakes (accounting for 46% of CH 4 emissions), but not for turbid lakes, where it only accounted for 2% of the emissions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Jeffrey et al (2019 a ) found that emissions from the emergent vegetated habitat accounted for 59% of the annual CH 4 emissions in an Australian subtropical wetland, followed by diffusion (21%) and ebullition (20%). Kyzivat et al (2022) also demonstrated the importance of including emergent macrophyte emissions, since accounting for their coverage increased lake CH 4 emission estimates by more than 21% in a subarctic‐boreal region. In our study, CH 4 emission from the vegetated habitat was also a very important pathway in clear lakes (accounting for 46% of CH 4 emissions), but not for turbid lakes, where it only accounted for 2% of the emissions.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, and independently of the state, emergent macrophytes (EM) play a significant role in GHG emissions (Bastviken et al 2004; Desrosiers et al 2022; Kyzivat et al 2022). They provide part of the carbon necessary to produce CH 4 in the sediments, but they also transport CH 4 from the sediments to the atmosphere and O 2 from the atmosphere to the sediments, which allows them to survive in anoxic sediments (Chanton 2005).…”
mentioning
confidence: 99%